Design of Controller for Large-Scale Uncertain Systems Adopting Affine Arithmetic - DORA, H MALLESAM (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 7 No 3 & 4 (2020): Journal of Advanced Research in Instrumentation and Control Engineering(ISSN: 2456-1398), 2021)
In this article presents a new controller design technique for large scale uncertain systems. The new controller is designed through a reduced order system from certain high order system. In the projected reduction method, the numerator coefficients are obtained with γ -table while the denominator polynomial is achieved with δ - table. An optimised reduced order model is derived with minimum value of ISE. In this proposed method gives better stability of the reduced order model, if consider the original stable high order system. A PID controller is designed for the high order original systems through its proposed reducer order model. Consider several numerical examples are available in the literatureto illustrate the usefulness of the proposed method andit gives sufficientoutcome. How to cite this article: Dora HM, Narasimhulu T, Pasumarthi MR. Design of Controller for Large-Scale Uncertain Systems Adopting Affine Arithmetic. J Adv Res Instru Control Engg 2020; 7(3&4): 1-4. DOI: https://doi.org/10.24321/2456.1398.202002